Aplikasi Augmented Reality berbasis Gamifikasi untuk Meningkatkan Pemahaman Matematika Siswa Sekolah Dasar - sani, Khairul Sani; Ita, Ita Fitriati; Ningsih, Nur Fitrianingsih; Ghazali, Muhammad Ghazali (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
At the elementary school level, problem-solving creativity is a key aspect in developing students' mathematical competencies. However, in daily learning practices, students are often only trained to solve routine problems that are procedural and minimal in variety, so that mathematical problem-solving skills in elementary schools require improvement and special attention. This study aims to develop innovative learning media in the form of an Augmented Reality (AR)-based application combined with gamification to enhance mathematical problem-solving creativity. AR technology allows for concrete and contextual visualization of mathematical concepts, while gamification elements such as scores and challenges are designed to build intrinsic motivation and make the learning experience enjoyable. The method used is Research and Development (R&D) by adapting the ADDIE (Analysis, Design, Development, Implementation, Evaluation) model. The process includes needs analysis, design, application development, implementation in schools, and evaluation of student creativity improvement. The results of product validation on five assessment aspects showed a very high level of validity, namely 91.8%. In terms of effectiveness, the average student problem-solving ability reached 66.5%. Furthermore, student responses to this game-based learning were very positive, with an average interest and motivation percentage of 93%. The study's conclusions indicate that this gamified AR application is not only valid and feasible to use, but also has the potential to significantly increase student engagement and foster creativity in solving mathematical problems at the elementary school level.